ANALYSIS OF THE IMPLEMENTATION OF THE SUPERVISORY FUNCTION OF THE INSPECTORATE AREAS IN WEST KUTAI REGENCY - Kornelis Itok; Musmuliadi Musmuliadi; Agustinus Djiu (International Journal Labs, 2022)
The problem in this study is whether the implementation of the regional government performance monitoring function carried out by the regional inspectorate in Kutai Barat has been carried out efficiently and effectively, and what factors affect the effectiveness of the implementation of the regional government performance function in Kutai Barat. The purpose of this research is to analyze the effectiveness of the implementation of the supervisory function of local government performance at the regional inspectorate of Kutai Barat, as well as to analyze the factors that affect the effectiveness of the implementation of its performance monitoring function. Based on the results of the analysis of the implementation of the supervisory function of the regional inspectorate in Kutai Barat, it can be concluded that the implementation of supervision, both from inspection, testing and investigation, has not been effective, this is due to the inaccuracy of time in carrying out supervision, the inaccuracy of the deviation data found for supervisory apparatus and the lack of human resources in this case is the government apparatus at the Kutai Barat Inspectorate Office in terms of quality and quantity. Factors that influence the implementation of the supervisory function on government administration in Kutai Barat include officers who have skills, knowledge in the field of work handled and in addition to the availability of facilities and infrastructure that support the implementation of supervision carried out by the Inspectorate office of Kutai Barat.